Nutritional Properties of Some Novel Selected Fish Species in Khuzestan Province, Iran - Aberoumand, Ali (Journal of Food Technology Research, 2014)
The proximate biochemical contents of some fish species i. e. Thunnus alalunga, Evynnis japonica, Caulerpa lentillifera, Orcynopsis unicolor and Euthynnus affinis were analyzed. Protein contents was determined in T. alalunga (22 %), E. japonica (13.02%), C.lentillifera (26.9%), O. unicolor (22%) and in E. affinis (24%) respectively. Fat content was recorded as 23.3%, 0.24%, 15%, 16% and 14% respectively in the five species of fish. The ash content was highest in C. lentillifera (8.8%). The present findings revealed that the highest protein content was recorded as in C.lentillifera (26.9%), but the fat was highest in T. alalunga (23.3%). The overall nutrient contents of studied medium indigenous fishes were observed as higher or equal to those of larger fish species.